Covalent β-lactoglobulin-maltodextrin amyloid fibril conjugate prepared by the Maillard reaction. (16th April 2021) - Karbasi, Mehri; Sánchez-Ferrer, Antoni; Adamcik, Jozef; Askari, Gholamreza; Madadlou, Ashkan; Mezzenga, Raffaele
Highlights: Amyloid fibrils (AF) from β-lg were conjugated with maltodextrin through the Maillard reaction. Analysis of free amino group and final products of Maillard reaction confirmed glycation. Maillard reaction did not change β-sheet content, contour length and rigidity of AFs. 1 h glycated sample showed the highest cross section and colloidal stability at pH 4. Prolonged reaction periods hydrolyzed the attached saccharides and decreased fibrils' height. Abstract: The surface modification of β-lactoglobulin amyloid fibrils (AFs) was investigated by performing the Maillard reaction with the free anomeric carbon of the maltodextrin in water at pH 9.0 and 90 °C. The bonding of maltodextrin to fibrils was confirmed by determining the free amino group content and the presence of final products from the Maillard reaction. The secondary structure of AFs was preserved as observed by circular dichroism analysis. Atomic force microscopy evidenced that prolonged heat treatment caused hydrolysis of the attached polysaccharide and consequently lowered the height of the fibrils from 8.0 nm (after 1 h) to 6.0 nm (after 24 h), which led to the reduction of hydrophilicity of resulting conjugate. Increasing the reaction time, however, resulted in the improvement of colloidal stability and decrease in turbidity ascribed to the increment of glycation degree, as well as, a decrease in the isoelectric point of the protein-based supramolecular object.